An overview on the recently discovered iota-carbonic anhydrases - Alessio Nocentini; Claudiu T. Supuran; Clemente Capasso (Taylor & Francis Group, 2021)
Carbonic anhydrases (CAs, EC 4.2.1.1) have been studied for decades and have been classified as a superfamily of enzymes which includes, up to date, eight gene families or classes indicated with the Greek letters α, β, γ, δ, ζ, η, θ, ι. This versatile enzyme superfamily is involved in multiple physiological processes, catalysing a fundamental reaction for all living organisms, the reversible hydration of carbon dioxide to bicarbonate and a proton. Recently, the ι-CA (LCIP63) from the diatom Thalassiosira pseudonana and a bacterial ι-CA (BteCAι) identified in the genome of Burkholderia territorii were characterised. The recombinant BteCAι was observed to act as an excellent catalyst for the physiologic reaction. Very recently, the discovery of a novel ι-CAs (COG4337) in the eukaryotic microalga Bigelowiella natans and the cyanobacterium Anabaena sp. PCC7120 has brought to light an unexpected feature for this ancient superfamily: this ι-CAs was catalytically active without a metal ion cofactor, unlike the previous reported ι-CAs as well as all known CAs investigated so far. This review reports recent investigations on ι-CAs obtained in these last three years, highlighting their peculiar features, and hypothesising that possibly this new CA family shows catalytic activity without the need of metal ions.